THE USE OF ECONOMIC AND SOCIAL EXCHANGE PERSPECTIVES IN LINKING SALARY SATISFACTION, WORK RELATIONSHIP, AND EMPLOYEE PERFORMANCE - Nikodemus Hans Setiadi Wijaya; Wa Ode Nur Hasana Rezeki (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The purpose of the current study is to propose the relationships among salary satisfaction, work relationship, and employee performance. A three-dimension of employee performance (i.e., task, adaptive, and contextual) is used in this study. The triachy measure of individual performance is suggested as a comprehensive measure to be employed in the business-oriented context. Economic- and social exchange theory were used to conceptualize the proposed hypotheses. A total of 118 responses from employees of an Indonesian company were analyzed in the hypotheses testing. The results suggested that both salary satisfaction and work relationship were positively related to employee performance. The independent variables were also positively related to all dimensions of employee performance. Furthermore, work relationship moderated the salary satisfaction-employee performance relationship. Theoretical and practical implications as well as the limitation of this study are discussed. Overall, this work advises that salary satisfaction and relationship at work are both necessary for employe performance improvement. Keywords: salary satisfaction, work relationhsip, employee performance, economic exchange theory, social exchange theory